ANALYSIS OF THE THERMOPSIS TURCICA PLANT - Safokulov Bobur,,; Khusankhonov Azizkhon,; Ayozov Shohabbos, (TADQIQOTLAR, 2025)
Background and Aims: Thermopsis turcica is an endemic species present in Türkiye  and  it  is  seen  as  a  source  of  functional  compounds  such  as  antioxidant phenolics. Even though some biological activities of the aerial parts of T. turcica have been determined, knowledge regarding the organ-specific chemical composition and effects on human breast cancer is still scarce. Therefore, the present study aims to evaluate  the  antioxidant  capacities,  phenolic  acid  profiles,  and  potential  biological activities of methanol extracts obtained from the leaf, flower, and stem tissues of T. turcica